Peran Guru dalam Menanamkan Nilai Karakter Kejujuran di Sekolah Dasar: Studi Pustaka - Lhutfia Wahyu Safutri; Rizki Aulia Ramadani (STKIP PGRI Bandar Lampung, 2026)
Instilling the character value of honesty is a key aspect of elementary education. One fundamental value that requires in-depth attention is honesty. Currently, various problems such as cheating and a lack of honest ethics among students persist. This article aims to analyze the role of teachers in instilling the value of honesty in elementary school students. The method used in this study is a descriptive qualitative research method through a literature study approach by collecting and analyzing various journals, books, and previous research relevant to the topic. The results of the analysis indicate that teachers play a strategically important role, not only as conveyors of academic material but also acting as good role models and can foster intrinsic motivation within students. Strategies that can be implemented by teachers include through role models and self-habituation, storytelling methods, and creating a learning environment that support character development.